Planning and execution of handball goalkeepers training: a descriptive study in youth categories teams in Brazil - Julie Hellen de Barros da Cruz; Rose Méri Santos da Silva; Tamires Carvalho Motta; Rafael Pombo Menezes; Rodolfo Novellino Benda; Gabriel Gustavo Bergmann (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This study aimed to describe how specific training for goalkeepers of youth handball teams is planned and executed in Brazil. Methods: This cross-sectional descriptive and quantitative study was based on information from 134 coaches responsible for specific training of handball goalkeepers for youth (under 12 - U12; U14; U16; and U18) teams. The selection of participants was non-randomly for convenience, using the virtual snowball method. The information was obtained through an online self-completion questionnaire carried out by the Google Forms platform. The questionnaire data were tabulated and assessed using the SPSS statistical program, and the information was presented using descriptive statistics. Results: The results show that specific training of goalkeepers occurs in 71.1% of youth handball teams. About the structure of the specific training session, most of it is performed 1 or 2 times a week (70.9%), lasting from 25 to 60 min (73.9%) and given by the team's leading coaches (77.6%). More than half of the participants stated that the training session occurs with the goalkeepers and the person in charge (55.2%). Most participants (69.4%) stated that the teams analyze and assess the goalkeepers' performance, and the training planning takes place weekly (39.6%). Conclusion: This data provides essential information that partially fills gaps in the literature and allows researchers and coaches to reflect on their practices, considering the importance of planning specific training for goalkeepers.